2008
DOI: 10.2320/matertrans.mer2008225
|View full text |Cite
|
Sign up to set email alerts
|

Room Temperature Aging Characteristic of MgLiAlZn Alloy

Abstract: Making alloys of Mg and Li is quite a task as their individual melting temperatures are vastly different. However, it is thought paid off considering their extreme lightness. Basically, low melting temperature Li could cause Mg-Li alloys' microstructures change at room temperature (R.T.). Recrystallization and aging of Li-rich solid solution phase () can proceed under R.T. Previously, R.T. aging phenomenon was mentioned without in-depth analysis. This paper fills up the blank by working on Mg-11.2%Li-0.95%Al-0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Still it is hoped to improve the strength through heavy rolling and heat treatment. Hsu et al pointed out that in the MgLiAlZn alloy, precipitation can proceed under room temperature, but it does not produce conspicuous hardening effect [4]. On the other hand, solid-solution strengthening does work.…”
Section: Introductionmentioning
confidence: 98%
“…Still it is hoped to improve the strength through heavy rolling and heat treatment. Hsu et al pointed out that in the MgLiAlZn alloy, precipitation can proceed under room temperature, but it does not produce conspicuous hardening effect [4]. On the other hand, solid-solution strengthening does work.…”
Section: Introductionmentioning
confidence: 98%
“…Previous papers 2,3) showed that the tensile strength of Mg alloy could be enhanced and the ductility would decrease after the implementation of supersaturated solution treatment. This was inferred that the supersaturated ¢ phase had an obvious contribution to the strength of MgLiAl alloy in comparison with the precipitation of ª phase.…”
Section: Introductionmentioning
confidence: 99%
“…Because the Al content of b phase at room temperature is almost zero for a Mg-12 wt pct Li alloy, [8] it can be deduced that the increase in the hardness was mainly due to solution hardening, which resulted from the dissolution of intergranular a during annealing at 250°C and thus a raised Al concentration in the b matrix up to 0.35 wt pct, as predicted by a calculated Mg-Li-Al phase diagram. [8] A recent report [7] also suggested that the supersaturated solid solution bearing lattice strain should account for the strengthening of this alloy rather than h phase precipitation. The move of the b peak to a slight higher angle in the XRD patterns (Figure 1), which implies that more Al was dissolved in the b matrix, somewhat supports this.…”
mentioning
confidence: 96%
“…The existence of the h phase has been demonstrated by transmission electron microscopy analysis in the same alloy subsequent to solution treatment and a short period of room-temperature aging. [7] This implies that h herein may form during room-temperature storage. Typical tensile stress-strain curves (Figure 2) all show a serrated flow feature caused by dynamic strain aging.…”
mentioning
confidence: 99%